Analisis Semiotika Representasi Penyintas Pelecehan Seksual Film Like & Share - Rinaldi, Keyza Baby; Aulia, Sisca (Koneksi, 2024)
The film "Like & Share" is a teenage drama film from Indonesia. The movie narrates the experiences of two friends named Lisa, portrayed by Aurora Ribero, and Sarah, portrayed by Arawinda, as they navigate through their lives and explore their sexuality together. However, the two of them experienced many obstacles in their friendship and also in their traumatic romance. Sarah, who is in a relationship with Devan, experiences sexual thoughts carried out by her boyfriend. In this study, qualitative methods are employed, utilizing John Fiske's semiotic analysis techniques to investigate, scrutinize, and explore the degrees of reality, representation, and ideology in the film Like & Share. The film Like & Share shows acts of sexual violence and what the survivors did in dealing with this problem with persuasive communication so that the victim made peace with the situation by giving a peace statement, but Sarah, as the perpetrator of the sexual disclosure, did not want to embrace it and Sarah took revenge accompanied by her best friend. Lisa. Film “Like & Share” merupakan film drama remaja yang berasal dari Indonesia, film ini berkisah tentang dua orang sahabat bernama Lisa yang diperankan oleh Aurora Ribero dan Sarah yang diperankan oleh Arawinda yang sedang mengeksplorasi kehidupan dan seksualitas mereka bersama. Tetapi banyak rintangan yang mereka berdua alami dalam persahabatan dan juga dalam percintaan yang traumatis. Sarah yang tengah menjalin hubungannya dengan Devan mengalami pelecehan seksual yang dilakukan oleh kekasihnya sendiri. Penelitian ini menggunakan metode kualitatif dengan teknik analisis semiotika John Fiske guna mengetahui, menelaah, dan mendalami level realitas, level representasi, dan level ideologi dalam film Like & Share. Film Like & Share memperlihatkan tindakan pelaku kekerasan seksual dan apa yang dilakukan oleh penyintasnya dalam menghadapi masalah ini dengan komunikasi persuasif agar korban berdamai dengan keadaan tersebut dengan memberikan surat pernyataan damai namun Sarah sebagai penyintas pelecehan seksual tersebut tidak mau menerimanya dan Sarah membalas dendamnya ditemani oleh sahabatnya Lisa.